Native and Debranched Starch Modification Using Physico-Chemical Treatment to Increase Resistant Starch Content in Rice - Wulan, Siti Narsito; Widyaningsih, Tri Dewanti; Ekasari, Dian (Fakultas Teknologi Pertanian Universitas Brawijaya, 2007)
Besides dietary fiber, resistant starch is carbohydrate that escape human digestion system, therefore it has potential health benefits. A study on native and debranched starch from rice using physico-chemical treatment has been conducted. Physico chemical treatment used were autoclaving, extrusion and crosslinking. The result showed that debranched starch which was treated with autoclaving, extrusion and crosslinking had higher resistant starch content than native starch treated with the same physico chemical treatment. The best treatment with the highest resistant starch content was obtained from debranched starch treated with crosslinking. The physicochemical properties of the product were as follows: moisture content of 8,45%, ash content of 3,19%, starch content of 85,44%, resistant starch content of 3,67%, initial gelatinization temperature of 79,3oC, gelatinization temperature of 89,6oC, and maximum viscosity of 1478 AU.Key word: resistant starch, debranching, autoclaving, extrusion, crosslinking